The Nanhai trade : - Wang, Gungwu (Times academic press, 1998)
The Nanhai Trade was the ancient maritime trade between China and Southeast Asia. China's dealings with the West, at this time, extended as far as India and Ceylon and, with a stretch of the imagination, Persia. This study examines the various features of the trade with Southeast Asia, especially the economic background and the Chinese imperial and regional attitudes towards it during the eleven centuries before the foundation of the Sung dynasty in 960 - roughly the period from the Han dynasty to that of the T'ang.